Calculation information subsystem to the funding of safety improvement measures units conveyors - Kiktev, M. (Energy and Automation, 2015)
The proposed information system gives advice to the funding of research, design and commissioning work to improve safety belts assemblies, including tape, based on the probability of creating emergency hazards in pipeline installation. Studied economic efficiency evaluation method based on statistical indicators developed software user interface and database structure input.